2020
DOI: 10.9734/ejnfs/2020/v12i730252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traditional Processing Methods on the Nutritional Composition of Sorghum (Sorghum bicolour L. Moench) Flour

Abstract: Sorghum is a drought-resistant crop grown widely in various parts of India. It has low protein content, highly deficient in essential amino acids lysine and tryptophan and high anti-nutritional content. Therefore, keeping in view the present study aimed to determine the effect of traditional processing methods such as fermentation, malting and roasting on the proximate composition, anti-nutritional factors, protein digestibility and lysine content of sorghum. The results showed that ash content increased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
2
4
1
Order By: Relevance
“…This might be because of the loss of watersoluble nitrogenous compounds during rinsing, soaking of grains and utilization of protein for the growth and development of the embryo on germination of sorghum grains (Nour et al, 2015). However, the protein content of the malted sorghum grains found in this study was higher than the values reported for malted sorghum grains elsewhere (6.90%) (Tamilselvan & Kushwaha, 2020), which could be possibly to the difference in the genetic makeup and agronomic practices. The protein content obtained from unprocessed sorghum grains was similar to the value reported for sorghum grain varieties grown in Ethiopia (8.20 to 16.48%) (Tasie & Gebreyes, 2020).…”
Section: Proximate Composition and Energy Contents Of Assosa I Improved Sorghum Varietycontrasting
confidence: 94%
See 1 more Smart Citation
“…This might be because of the loss of watersoluble nitrogenous compounds during rinsing, soaking of grains and utilization of protein for the growth and development of the embryo on germination of sorghum grains (Nour et al, 2015). However, the protein content of the malted sorghum grains found in this study was higher than the values reported for malted sorghum grains elsewhere (6.90%) (Tamilselvan & Kushwaha, 2020), which could be possibly to the difference in the genetic makeup and agronomic practices. The protein content obtained from unprocessed sorghum grains was similar to the value reported for sorghum grain varieties grown in Ethiopia (8.20 to 16.48%) (Tasie & Gebreyes, 2020).…”
Section: Proximate Composition and Energy Contents Of Assosa I Improved Sorghum Varietycontrasting
confidence: 94%
“…In Ethiopia, sorghum is consumed without doing any efforts to minimize the antinutritional contents. However, there are premilling processing techniques that can help to reduce the high concentration of antinutritional factors to improve bioavailability of minerals and digestion of proteins (Samtiya et al., 2020; Tamilselvan & Kushwaha, 2020) and organoleptic properties (Oghbaei & Prakash, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More-over Okpala et al ( 2013) reported that fermented sorghum flour had a ash content of 1.96%. The values for protein of 7.97 g/100 g in this study for fermented sorghum flour are comparable to 7.60 g/100 g reported by Oboh & Amusan (2009), however they are higher than 6.90 g/100 g obtained by Tamilselvan & Kushwaha (2020) though lower than 9.77 g/100 g and 8.08 g/100 g reported by Afify et al (2012) and Okpala et al (2013) respectively.…”
Section: Nutritional Composition Of Fermented Sorghum Floursupporting
confidence: 69%
“…The crude fiber value of 1.80% is higher than 1.58% reported by , however the value is lower than 2.05% reported by Ojokoh & Eromosele (2015). The carbohydrate content of fermented sorghum flour reported in this study is similar to values obtained by Tamilselvan & Kushwaha (2020). In this study fermented sorghum flour had iron content of 2.62 mg/100g which is higher than 3.95 mg/100g obtained by Afify et al (2012).…”
Section: Nutritional Composition Of Fermented Sorghum Floursupporting
confidence: 58%
See 1 more Smart Citation